Microscopic Observations of Pulsating Aurora Associated With Chorus Element Structures: Coordinated Arase Satellite‐PWING Observations. Issue 22 (26th November 2018) - Ozaki, M.; Shiokawa, K.; Miyoshi, Y.; Hosokawa, K.; Oyama, S.; Yagitani, S.; Kasahara, Y.; Kasaba, Y.; Matsuda, S.; Kataoka, R.; Ebihara, Y.; Ogawa, Y.; et al.
Abstract: Rapid (<1 s) intensity modulation of pulsating auroras is caused by successive chorus elements as a response to wave‐particle interactions in the magnetosphere. Here we found that a pulsating auroral patch responds to the time spacing for successive chorus elements and possibly to chorus subpacket structures with a time scale of tens of milliseconds. These responses were identified from coordinated Arase satellite and ground (Gakona, Alaska) observations with a high‐speed auroral imager (100 Hz). The temporal variations of auroral intensity in a few‐hertz frequency range exhibited a spatial concentration at the lower‐latitude edge of the auroral patch. The spatial evolution of the auroral patch showed repeated expansion/contraction with tens of kilometer scales in the ionosphere, which could be spatial behaviors in the wave‐particle interactions. These observations indicate that chorus elements evolve coherently within the auroral patch, which is approximately 900 km in the radial and longitudinal directions at the magnetic equator. Plain Language Summary: This study shows a direct link between discrete chorus elements and intensity modulations in a pulsating auroral patch. Currently, it is widely believed that chorus waves play an important role in the generation of pulsating aurora. Many previous theoretical, simulation, and optical observation studies have suggested a one‐to‐one correspondence between successive chorus elements and intensity modulations of pulsating auroras in the frequency range of a few hertz. In this study, detailed spatiotemporal characteristics of a pulsating auroral patch were captured by coordinated observations between the Arase satellite and the ground‐based network from study of dynamical variation of Particles and Waves in the INner magnetosphere using Ground‐based network observations (PWING). The ideal conjugate observations reveal that a pulsating auroral patch responds to the time spacing of successive chorus elements and possibly to chorus subpacket structures with a time scale of tens of milliseconds. Furthermore, the intensity modulations of the pulsating aurora at a few‐hertz range were caused by the spatial variations of the pulsating auroral patch. Therefore, this study provides important information on understanding rapid (tens of milliseconds) resonant interaction processes between chorus waves and charged particles. Key Points: Coordinated Arase and ground observations reveal an association between a pulsating aurora and chorus at time scales less than 1 s The pulsating aurora shows a rapid (less than 1 s) spatiotemporal evolution related to chorus element structures The estimated spatial size of the source region is 900 km in the radial and longitudinal directions at the magnetic equator